"نموذج مقترح لقياس أداء إدارة النفايات في القطاع الصحي باستخدام معلومات التكلفة البيئية" (دراسة حالة: مشفى الباسل) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة إلى اقتراح نموذجاً لقياس أداء إدارة النفايات باستخدام التكلفة البيئية في القطاع الصحي في سورية, وقد اتبعت الدراسة منهج دراسة الحالة على مشفى الباسل في مدينة طرطوس لسهولة الحصول على البيانات التكاليفية اللازمة لإجراء الدراسة. تم جمع البيانات اللازمة للدراسة من خلال الملاحظة وتحليل المستندات والتقارير العائدة للمشفى إلى جانب إجراء المقابلات الشخصية مع المدراء ورؤساء الأقسام والمحاسبين في المشفى. توصلت الدراسة إلى وضع نموذج لقياس أداء إدارة النفايات في المشفى المدروس. كما بينت نتائج تطبيق النموذج على المشفى المدروس أنّ للنموذج المقترح دوراً فعّالاً في توفير معلومات كمية دقيقة تساهم في إجراء تقييم دقيق للأداء البيئي ككل, كما يعد انخفاض تكاليف التخلص من النفايات الطبية مؤشراً حقيقياً كمياً لتقييم أداء إدارة النفايات في المنشآت الصحية. كما توصي الدراسة بالتطبيق الفعّال للنموذج المقترح على مشفى الباسل. This study aimed to proposes a model for measuring the performance of waste management using the environmental cost in the health sector in Syria. A case study was selected at Basel Hospital in Tartous governorate for easy access to the required cost data for the study. The data needed for the study were collected through observation and analysis of documents and reports related to the hospital, as well as conducting interviews with managers, heads of departments and accountants at the hospital. The study led to the development of a proposed model for measuring waste management performance in the studied hospital. The results of applying the model to the hospital showed that, the proposed model has an effective role in providing accurate quantitative information that contributes to a thorough assessment of environmental performance as a whole. The low cost of disposal of medical waste is a real quantitative indicator for assessing waste management performance in health facilities hospital. The study recommended ineffective applying to the model on Al Basel hospital.